2015
DOI: 10.1002/sia.5762
|View full text |Cite
|
Sign up to set email alerts
|

XPS and factor analysis study of initial stages of cerium oxide growth on polycrystalline tungsten

Abstract: The initial stages of growth of the nanostructured cerium oxide deposited on the polycrystalline tungsten surface by pulsed laser deposition are studied using XPS technique. The population of Ce (III) and Ce (IV) oxidation states in the deposited CeO2−x layers is determined applying factor analysis method. Tungsten atoms react with oxygen from the cerium oxide nanoparticles already at the room temperature, and a layer of tungsten trioxide is formed at the interface. Gradual heating of the samples up to 900 K l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…The appearance of two peaks of Ce 3d 5/2 and Ce 3d 3/2 at binding energy ranges of 878–893 eV and 894–912 eV, respectively, indicates the presence of both Ce 3+ and Ce 4+ components doped in Ti 3 C 2 MXene-Ce 3+ . , As stated earlier, the encapsulation of Ti 3 C 2 MXene was performed in an aqueous solution at pH 8. In this medium, owing to the presence of O 2 , H 2 O, OH – , and H 2 O 2 as an oxygen reduction intermediate, a portion of Ce 3+ ions is turned to Ce 4+ ions (eqs and ). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of two peaks of Ce 3d 5/2 and Ce 3d 3/2 at binding energy ranges of 878–893 eV and 894–912 eV, respectively, indicates the presence of both Ce 3+ and Ce 4+ components doped in Ti 3 C 2 MXene-Ce 3+ . , As stated earlier, the encapsulation of Ti 3 C 2 MXene was performed in an aqueous solution at pH 8. In this medium, owing to the presence of O 2 , H 2 O, OH – , and H 2 O 2 as an oxygen reduction intermediate, a portion of Ce 3+ ions is turned to Ce 4+ ions (eqs and ). , …”
Section: Resultsmentioning
confidence: 99%
“…In this medium, owing to the presence of O 2 , H 2 O, OH − , and H 2 O 2 as an oxygen reduction intermediate, a portion of Ce 3+ ions is turned to Ce 4+ ions (eqs 15 and 16). 45,46 3.2.2. FT-IR and TGA.…”
Section: Methodsmentioning
confidence: 99%
“…8b), suggesting that the W 6+ is the main tungsten valence. 50 The Sn 3d XPS spectra of the CeWSnO x -800 catalyst showed spin–orbit peaks at 495.1 and 486.7 eV (Fig. 8c), respectively, which indicated that the Sn species on the surface were in the form of Sn 4+ .…”
Section: Resultsmentioning
confidence: 94%
“…45 The u 000 , u 00 , u, v 000 , v 00 , v peaks were associated to the Ce 4+ state while the u 0 , u 0 , v 0 and v 0 peaks were attributed to the Ce 3+ state. [46][47][48] As can be appreciated in Table 2, the fresh doped samples show a signicant increase in supercial Ce 3+ with respect to the CeZr sample. This suggests that the atoms of the transition metals can enter into the CeZr lattice and then Ce 4+ can be partially converted to Ce 3+ .…”
Section: Materials Characterizationmentioning
confidence: 81%